Guidance for the risk assessment of the presence at low level of genetically modified plant material in imported food and feed under Regulation (EC) No 1829/2003. (20th November 2017) - ,; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: This document provides guidance for the risk assessment under Regulation (EC) No 1829/2003 of the unintended, adventitious or technically unavoidable presence in food and feed of low level of genetically modified plant material intended for markets other than in the European Union. In this context, the presence at low level is defined to be maximum 0.9% of genetically modified plant material per ingredient. This guidance is intended to assist applicants by indicating which scientific requirements of Annex II of Regulation (EU) No 503/2013 are considered necessary for the risk assessment of the presence at low levels of genetically modified plant material in food and feed. Abstract : This publication is linked to the following EFSA Supporting Publications article:http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1329/full